2014
DOI: 10.1074/jbc.m114.573824
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Activates TORC2-Gad8 Protein via Positive Regulation of the cAMP/cAMP-dependent Protein Kinase A (PKA) Pathway and Negative Regulation of the Pmk1 Protein-Mitogen-activated Protein Kinase Pathway

Abstract: Background: TORC2 is a conserved protein complex that regulates multiple aspects of cell survival and proliferation. Results: Gad8 is regulated by the cAMP-dependent protein kinase A and the Pmk1 protein-mitogen-activated protein kinase. Conclusion: Glucose is a major regulator of TORC2-Gad8 signaling. Significance: Identification of a novel mode of regulation of TORC2-Gad8 in response to glucose and stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 64 publications
1
45
1
1
Order By: Relevance
“…61 In contrast, our repeated experiments detected no significant defect in the Gad8 phosphorylation among the cAMP-PKA pathway mutants tested in this study, including Dgit3, Dgpa2 and Dpka1. Because Cohen et al prepared the cellular protein extract under non-denaturing condition without phosphatase inhibitor, it is conceivable that Gad8 was dephosphorylated by phosphatases in the crude extract.…”
Section: Discussioncontrasting
confidence: 42%
“…61 In contrast, our repeated experiments detected no significant defect in the Gad8 phosphorylation among the cAMP-PKA pathway mutants tested in this study, including Dgit3, Dgpa2 and Dpka1. Because Cohen et al prepared the cellular protein extract under non-denaturing condition without phosphatase inhibitor, it is conceivable that Gad8 was dephosphorylated by phosphatases in the crude extract.…”
Section: Discussioncontrasting
confidence: 42%
“…In addition, the TORC2 complex favors de novo Pck2 synthesis during stress, which is necessary to allow Pmk1 activation in response to specific environmental insults, such as cell wall stress or glucose limitation. Although TORC2-Gad8 signaling is required for adequate cellular response to stress, it has been shown recently that the CIP negatively regulates the TORC2-Gad8 pathway (Cohen et al, 2014). Therefore, we envisage a scenario where TORC2 will positively influence CIP signaling but will subsequently undergo CIP-mediated inhibition, thus modulating the stress response in a highly dynamic and flexible fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most if not all of the cellular functions of S. pombe TORC2 are mediated via phosphorylation and activation of its downstream substrate Gad8, an AGC (PKA, PKG, and PKC kinases)-like kinase with structural and functional similarities to AKT, the most well established substrate kinase of mTORC2 (11,14,15). Although S. pombe TORC1 is responsive to the availability of nitrogen or amino acids (5)(6)(7)(8)16), we (17) and the Shiozaki and co-workers (18) have recently shown that S. pombe TORC2 responds to the availability of glucose. Upon glucose withdrawal or shift from glucose to a less favorable carbon source such as glycerol, there is a reduction of TORC2-dependent phosphorylation of Gad8 at serine 546 (equivalent to serine 473 in AKT) and concomitant reduced Gad8 kinase activity (17,18).…”
Section: Target Of Rapamycin (Tor)mentioning
confidence: 99%
“…Although S. pombe TORC1 is responsive to the availability of nitrogen or amino acids (5)(6)(7)(8)16), we (17) and the Shiozaki and co-workers (18) have recently shown that S. pombe TORC2 responds to the availability of glucose. Upon glucose withdrawal or shift from glucose to a less favorable carbon source such as glycerol, there is a reduction of TORC2-dependent phosphorylation of Gad8 at serine 546 (equivalent to serine 473 in AKT) and concomitant reduced Gad8 kinase activity (17,18). Thus, S. pombe TORC1 and TORC2 play essential roles in regulating growth by responding to two distinct key nutritional cues.…”
Section: Target Of Rapamycin (Tor)mentioning
confidence: 99%
See 1 more Smart Citation